Crop Yield Prediction Using Random Forest Based on Soil, Climate, and Agronomic Factors - Putu Sugiartawan; I Nyoman Darma Kotama; Anak Agung Surya Pradhana (INFOTEKS (Information Technology, Computer and Sciences), 2026)
Agricultural yield prediction plays a critical role in ensuring food security and optimizing farming practices. Traditional methods of crop yield estimation often rely on expert knowledge and historical data, which can be limited and inaccurate. Machine learning algorithms, particularly Random Forest, have shown promise in improving the accuracy of crop yield predictions by considering complex interactions between soil, climate, and agronomic factors. This study aims to develop a Random Forest-based model to predict crop yield using a diverse set of agricultural datasets. The model was trained and validated using data from multiple regions, focusing on soil properties, climatic conditions, and farming practices. The results demonstrated that the Random Forest model provided reliable predictions, with performance evaluated using metrics such as MAE, RMSE, and R². However, some discrepancies between actual and predicted values were observed, indicating room for improvement. Future work will focus on integrating real-time data, such as soil moisture and pest infestation, to enhance the model's accuracy. Additionally, exploring advanced machine learning techniques like deep learning could provide better handling of complex patterns in agricultural data. This research contributes to the growing field of agricultural data science and aims to provide a scalable solution for crop yield prediction across various regions.